MACROPRUDENTIAL STRESS TESTING OF CREDIT RISK: MULTI-LEVEL CAPITAL ADEQUACY RATIO ON INDONESIAN BANKING SECTOR - Kurniawati, Shilvia
Macroprudential policy is implemented to foster financial stability in the financial system, and stress testing process is used as a regular assessment of the resilience level of given shock scenarios. This study tries to design a credit risk stress testing on Indonesia’s monthly empirical data that can be used for macroprudential monitoring and to obtain indicator outcome in the macroprudential policy. In this work, we construct macroeconomic scenarios, then link them to credit risk factor, and estimate the outcome indicator to measure banks’ resilience. The result is reported that an economic risk weighted capital adequacy ratio (ERW-CAR) classified on banks’ multilevel business activity provides a more optimal level under different scenarios, compared to the current regulatory capital adequacy ratio (CAR) because the banks more utilize the core capital to business activity opportunity. In the historical and predicted scenario, banks based on business activities are all sufficiently safeguarded and the ERW-CARs are closely to the current regulatory. They have adequate capital to accomodate the macroprudential supervisor based-requirement adjusted with economic condition one year ahead. Under stress scenarios, the ERW-CAR of banks based on business activity declines substantially and as expected to still stand above the minimum requirement of regulation. The findings also reveal that the ERW-CAR is more sensitive to sudden changes in lending rates.